5x+13=-5(2+2x)-8x

Simple and best practice solution for 5x+13=-5(2+2x)-8x equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5x+13=-5(2+2x)-8x equation:


Simplifying
5x + 13 = -5(2 + 2x) + -8x

Reorder the terms:
13 + 5x = -5(2 + 2x) + -8x
13 + 5x = (2 * -5 + 2x * -5) + -8x
13 + 5x = (-10 + -10x) + -8x

Combine like terms: -10x + -8x = -18x
13 + 5x = -10 + -18x

Solving
13 + 5x = -10 + -18x

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '18x' to each side of the equation.
13 + 5x + 18x = -10 + -18x + 18x

Combine like terms: 5x + 18x = 23x
13 + 23x = -10 + -18x + 18x

Combine like terms: -18x + 18x = 0
13 + 23x = -10 + 0
13 + 23x = -10

Add '-13' to each side of the equation.
13 + -13 + 23x = -10 + -13

Combine like terms: 13 + -13 = 0
0 + 23x = -10 + -13
23x = -10 + -13

Combine like terms: -10 + -13 = -23
23x = -23

Divide each side by '23'.
x = -1

Simplifying
x = -1

See similar equations:

| -50.5+-96.8-1.6y+24.2+y=190 | | eln(2x-3)=1 | | 5+x-3=3x | | Y=2x4-128/152 | | 12c-7-3c+9= | | 6x^2-36x-96=0 | | 8z+6z= | | 2ln(2x-3)=2 | | 32=-16t+56t | | x^2+y^2+12x+4y+36=0 | | 2s+7s= | | 21y+7y= | | 2x+x+10=55 | | 86x+5x-8y-800=500 | | 5p+5p= | | 3x(x-2)=-1.5 | | 13b+7b= | | 4w+2=4w+7 | | 2x+8-3=11+11+11 | | w*3=7 | | 29r+4=28+1r | | (w/(2w-3))=4/w | | 4x^2+24x+4y^2+4y-363=0 | | 6x-39=3x+42+11x | | 5.98t=1.4t-13.53 | | 2r(x-3)=15 | | a=6-2b | | 6x+9-8(x+1)=3x+5 | | -2=-(n-a) | | x*4=15 | | 5x+13=5(2+2x)-8x | | (x+3)2=-3+k |

Equations solver categories